Predictive Model for Successful Product Mix in Trade Outlets using Genetic Algorithm and Association Rule Mining - V.Ramalingam, V.; Jha, Viplav Vijay; Pandian, A. (International Journal of Engineering and Technology, 2018)
Supermarket chains seem to be have a humongous amount of data. Aprioi algorithm is considered to be the classic way to create associations in the data and create power combination of products that would occupy a particular shelf and area. This algorithm employs the greedy method to create meaningful associations between data. This mechanism, however , has a very high time complexity. Its time complexity is linearly proportional to the product of number of transactionsÂ Â and the average number of products bought per transaction, thus creating computations that can only be solved in polynomial time when compared to the logarithmic-time complexity algorithm which we employ in this paper.Â Â